Reflection seismic investigations on south Gotland, Sweden, to evaluate CO2 storage strategies - Juhlin, Christopher; Erlström, Mikael; Hedin, Peter; Brodic, Bojan; Sopher, Daniel (Solid Earth, 2025)
Reflection seismic data were acquired in the Sudret area of Gotland between 6 and 13 November 2023. Objectives of the survey were to obtain images of the subsurface down to the Precambrian basement in the vicinity of two cored boreholes that had been drilled earlier down to about 800 m. The seismic profiles were positioned to provide a better understanding of the sedimentary strata and local structure near the two boreholes. It was also hoped that they could be used to correlate the properties of the geological formations offshore for studying the potential of future geological storage of CO2 within Swedish waters. For these purposes a sparse 3D survey was acquired that covered a ca. 300 m by 700 m rectangular area with high fold, including the locations where the boreholes were drilled. A longer ca. 2.8 km 2D profile was also acquired adjacent to the 3D survey that ran roughly in a N–S direction. In addition, distributed acoustic sensing (DAS) measurements were performed in the two cored boreholes. We report here on some results from the 2D and 3D surveys and from the DAS measurements, incorporating information from the core and sonic logs. Numerous semi-continuous reflection horizons are observed in the ca. upper 500 ms after stacking. A particularly strong reflection at about 330 ms likely originates from the top of Ordovician limestones. Generation of synthetic seismograms based on the acquired sonic logs in the two boreholes confirms this interpretation. Cambrian sandstones are also reflective, as well as shallow sandstone layers in the upper 150 ms. Normal moveout (NMO) velocities are relatively constant at about 3500 m s−1. However, depth conversion using this velocity places the reflectivity deeper than is expected from the well data. In comparison, using the DAS data, the vertically propagating P-wave velocity can be measured at an average 3100 m s−1 from the surface to 580 m depth. Using this velocity for depth conversion provides more reasonable depths to the main horizons. Since the NMO velocities are largely controlled by the horizontal velocity of the rock the difference between these and the DAS velocity can be explained by the rocks in the area having significant anisotropy. Seismic modeling indicates that a horizontal velocity of about 3500 m s−1 is necessary to explain the difference between the NMO velocity and the vertical velocity. This corresponds to an anisotropy of about 13 %. This may be important to take into account when acquiring and processing future, or legacy, offshore seismic data for the purpose of mapping potential structures or formations for CO2 storage.